Agatha Christie's Poirot. Collector's set 8 [videorecording (DVD)] - Eastman, Brian; Bruce, John; Farnham, Brian; Grieve, Ken; Suchet, David; Fraser, Hugh; Jackson, Philip, 1948-; Moran, Pauline; Christie, Agatha, 1890-1976 (Agatha Christie's Poirot., 2003)
"The Case of the Missing Will: Poirot is the executor of a revised will that disappears when its author dies suddenly. The Adventure of the Italian Nobleman: Hastings' decision to buy an elegant Italian car coincides with a case involving an Italian count. The Chocolate Box: A trip home to Belgium with Japp causes Poirot to reopen a case that he failed to solve 20 years earlier."--Container